14.2k views
3 votes
Find the midpoint given the points: (3,9) and (-1,-5)

2 Answers

4 votes

Answer:

(1, 2 )

Explanation:

Given endpoints (x₁, y₁ ) and (x₂, y₂ ) then the midpoint is

[
(x_(1)+x_(2) )/(2) ,
(y_(1)+y_(2) )/(2) ]

let (x₁, y₁ ) = (3, 9) and (x₂, y₂ ) = (- 1, - 5) then

midpoint = (
(3-1)/(2) ,
(9-5)/(2) ) = (1, 2 )

User Mark Pearl
by
4.8k points
7 votes

Answer:

(1,2)

Explanation:

use the equation

(x,y) midpoint = ( x1 + x2/ 2), (y1 + y2 / 2 ) )

User Jaydeep Khamar
by
4.9k points